Cancer immunotherapy comes of age and looks for maturity - Amanda Finck (Nature Portfolio, 2020)
As Nature Communications celebrates a 10-year anniversary, the field has witnessed the transition of cancer immunotherapy from a pipe dream to an established powerful cancer treatment modality. Here we discuss the opportunities and challenges for the future.